Esthetic management of a patient with cleft lip and palate - Garain, Ridyumna; DV, Swapna; G, Nivaskumar; SN, Prakruthi; B, Vedavathi (Indian Journal of Case Reports, 2022)
Esthetic rehabilitation of cleft lip and palate patients presents a myriad of challenges and requires interdisciplinary coordination. In the present case report, a 22-year-old male patient with a cleft palate and alveolus was treated. Comprehensive multidisciplinary treatment planning and management, along with a clinician-friendly process of smile designing and of creating mock-ups using digital technology, helped overcome the esthetic challenges faced in this case.